2022
DOI: 10.3389/fpsyg.2021.709208
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dance-Based Interventions on Depression for Persons With MCI and Dementia: A Systematic Review and Meta-Analysis

Abstract: Background: There is a growing need to offer appropriate services to persons with mild cognitive impairment (MCI) and dementia who are faced with depression and anxiety distresses beyond traditional pharmacological treatment. Dance-based interventions as multi-dimensional interventions address persons' physical, emotional, social, and spiritual aspects of well-being. However, no meta-analysis of randomized controlled treatment trials (RCTs) has examined the effectiveness of dance-based interventions on depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Various neuroimaging studies of dance observation showed that DMT can improve the neuronal connectivity in specific brain regions of older participants' brain, promote neuroplasticity, and induce changes in gray and white matter in multiple brain regions, especially the frontotemporal region. Previous studies suggested DMT as a rehabilitation tool of disease management and clinical improvement for patients with AD (Mabire et al, 2019 ; Ruiz-Muelle and López-Rodríguez, 2019 ), MCI (Liu et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ), and PD (Barnish and Barran, 2020 ; Berti et al, 2020 ; Carapellotti et al, 2020 ; de Almeida et al, 2020 ; Emmanouilidis et al, 2021 ; Ismail et al, 2021 ). The pooled results of the latest meta-analysis of the efficacy of DMT in PD patients showed that DMT can improve motor function and reduce the burden on caregivers (Emmanouilidis et al, 2021 ; Ismail et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various neuroimaging studies of dance observation showed that DMT can improve the neuronal connectivity in specific brain regions of older participants' brain, promote neuroplasticity, and induce changes in gray and white matter in multiple brain regions, especially the frontotemporal region. Previous studies suggested DMT as a rehabilitation tool of disease management and clinical improvement for patients with AD (Mabire et al, 2019 ; Ruiz-Muelle and López-Rodríguez, 2019 ), MCI (Liu et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ), and PD (Barnish and Barran, 2020 ; Berti et al, 2020 ; Carapellotti et al, 2020 ; de Almeida et al, 2020 ; Emmanouilidis et al, 2021 ; Ismail et al, 2021 ). The pooled results of the latest meta-analysis of the efficacy of DMT in PD patients showed that DMT can improve motor function and reduce the burden on caregivers (Emmanouilidis et al, 2021 ; Ismail et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by Ko et al [37], laughing decreased significantly GDS-15 scores in elderly. Wang et al [57] confirmed this point within a meta-analysis that dance-based interventions cope significantly with depression for persons with MCI and dementia. These findings are contradictory with a meta-analysis results conducted by Wu et al [41].…”
Section: Discussionmentioning
confidence: 80%
“…Irish country, African, Greek, and other types of dances were included with medium physical intensity; enhanced brain activity on resting state fMRI with the dance intervention correlated with improved attention and executive functions. Depression in people with MCI and dementia was reduced with dancing [120]. Traditional dances of India improved balance and motor skills more than neuromuscular training in "children with Down syndrome" [121]; the benefits of dance can also be facilitated remotely [122].…”
Section: Dancementioning
confidence: 99%